PENGARUH KUALITAS PRODUK DAN ONLINE CUSTOMER REVIEW TERHADAP MINAT BELI KONSUMEN PADA RIDHO BAKSO BAKWAN MALANG DI BINTARO - Adiva Salsabila; Irmal Irmal (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstract. This study aims to determine the effect of Product Quality (X1) andOnline Customer Review (X2) on Consumer Purchase Interest (Y) at Ridho BaksoBakwan Malang in Bintaro, both partially and simultaneously. The research methodused is the associative method with a quantitative approach and a sample of 95respondents. The results show that Product Quality has a positive and significant effecton Consumer Purchase Interest, as evidenced by the t-value (9.020) > t-table(1.661) and significance value (< 0.001) < (0.05). Similarly, OnlineCustomer Reviews also have a positive and significant effect, with a t-value(11.225) > t-table (1.661) and a significance value (< 0.001) < (0.05). Furthermore, simultaneously, both variables positively and significantly influenceConsumer Purchase Interest, as evidenced by the F-test with an F-count value (77.175) > F-table(3.094) and a significance value (< 0.001) < (0.05). This finding is reinforced by theCoefficient of Determination (R2) of 0.627, which confirms that 62.7% of the variation inConsumer Purchase Interest is explained by Product Quality and Online Customer Reviews. Keywords: Product Quality, Online Customer Reviews, Consumer Purchase Interest.